TEACHERS’ ATTITUDES AND PROBLEMS OF USING ICT IN TEACHING EFL - Arif Aminullah; Bambang Apriady Loeneto; Machdalena Vianty (University of Kuningan, 2019)
The implementation of ICT is very important in education. By using ICT, the process of teaching and learning is more effective and efficient. The objectives of this research were (1) to find out the attitudes of English teachers of public senior high schools in Palembang towards the use of ICT in the process of teaching and learning English, and (2) to find out the problems that commonly faced by English teachers towards the use of ICT in the process of teaching and learning English. This research was conducted at 16 public senior high schools in Palembang. There were 19 respondents who were selected by using ‘purposive sampling’ technique. The data were collected by using questionnaire, interview, observation and documentation. The obtained data were analyzed in descriptive statistics. The statement checklist which used Likert scale was presented in the form of percentage while the results of answering descriptive questions was reported descriptively. The results showed that the attitudes of the teachers towards the use of ICT in the process of teaching and learning English were positive. However, some of them still faced many problems such as lack of ICT equipments, lack of competency, and also unsupported regulation from institution. Therefore, the facilities and infrastructures in each school and also the teachers’ ability and knowledge about the use of ICT need to be increased.